2015
DOI: 10.1103/physrevd.92.083516
|View full text |Cite
|
Sign up to set email alerts
|

Primordial gravitational waves and the collapse of the wave function

Abstract: "The self-induced collapse hypothesis" was introduced by D. Sudarsky and collaborators to explain the origin of cosmic structure from a perfect isotropic and homogeneous universe during the inflationary regime. In this paper, we calculate the power spectrum for the tensor modes, within the semiclassical gravity approximation, with the additional hypothesis of a generic self-induced collapse of the inflaton's wave function; we also compute an estimate for the tensor-to-scalar ratio. Based on this calculation, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
(91 reference statements)
0
18
1
2
Order By: Relevance
“…[51] one followed a different approach to the problem; the authors successfully applied the CSL collapse mechanism to the inflationary universe but within the semiclassical gravity framework. Consequently, as pointed out in [30,52], the amplitude of the primordial gravitational waves is exactly zero at first order in the perturbations. Therefore, a confirmed detection of primordial gravity waves would make this approach face serious issues.…”
Section: Introductionmentioning
confidence: 91%
“…[51] one followed a different approach to the problem; the authors successfully applied the CSL collapse mechanism to the inflationary universe but within the semiclassical gravity framework. Consequently, as pointed out in [30,52], the amplitude of the primordial gravitational waves is exactly zero at first order in the perturbations. Therefore, a confirmed detection of primordial gravity waves would make this approach face serious issues.…”
Section: Introductionmentioning
confidence: 91%
“…In the particular case of CSL theory, its first implementation into the primordial universe, based on the SCG framework, was done in [228], and some of us have continued to explore its consequences. For example, in [239,241,242] it was shown that a strong suppression of primordial B-modes in the CMB is predicted generically. In addition, within that same framework, observational constraints were analyzed in [238], and in [232] it was found that the condition for eternal inflation can be bypassed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in [32][33][34], and working in the context of semiclassical gravity, it was shown that the CSLIM predicts a strong suppression of primordial B-modes, i.e. the predicted amplitude of the tensor power spectrum is very small generically (undetectable by current experiments).…”
Section: Introductionmentioning
confidence: 99%